Legal Analysis of Marriage Dispensation Underage in Jagabita Village, Bogor, Using the Compilation of Islamic Law Approach - Fitri Nuraeni; Amin Songgirin (Mabadi Iqtishad Al Islami, 2024)
The analysis focuses on the legal aspects surrounding marriage dispensations for individuals below the age of 19, as outlined in Law Number 16 of 2019, which amends Law Number 1 of 1974 concerning Marriage. According to Article 7, paragraph (1) of the Marriage Law, marriage is permissible only if both the man and woman have reached the age of 19. This provision underscores the necessity of establishing a minimum age for marriage, considering the significant legal implications associated with marital unions, such as alterations in rights and responsibilities. However, a potential ambiguity arises when Article 7, paragraph (1) is juxtaposed with Article 6, paragraph (2) of the same law. While Article 7, paragraph (1) sets forth a minimum age requirement for marriage, Article 6, paragraph (2) does not provide clear legal guidance for individuals seeking marriage before reaching the prescribed age. Despite the provision for dispensation in Article 7, paragraph (2) and Article 6, paragraph (2), some argue that granting dispensations may overlook future familial harmony and reduce the institution of marriage to mere physical fulfillment, contradicting principles of Islamic jurisprudence. Data collection involved observations and interviews with local residents who entered into underage marriages, as well as discussions with the head of the Religious Affairs Office (KUA) of Parung Panjang Subdistrict. The research adopts a socio-legal approach, integrating sociological and juridical perspectives, within a qualitative field research framework. The study aims to comprehend the regulation of marriage dispensation under both civil and Islamic law, examining the consequences of underage marriages in Jagabita Village, Bogor.